Telehealth nursing : tools and strategies for optimal patient care - Martich, Dawna (Springer Publishing Company, LLC, 2017)
Includes all of the information necessary for safe, competent practice, this is a practical, hands-on educational and training resource for nurses working in telephonic health care settings. It delivers the requisite tools and instruction for optimizing patient communication, performing assessments, and providing effective care of chronic conditions. Moving step-by-step from simple to complex information, the resource de-mystifies the process of telephonic nursing care and describes numerous tools such as learning outcomes, algorithms, exercises to reinforce learning, case studies, and critical thinking questions that help readers develop and hone telehealth nursing skills. The text instructs nurses on how to actively listen to the patient "between the lines" in the absence of an in-person examination and discern the right questions to ask and tone to adopt. Chapters provide enhanced communication techniques to perform comprehensive health assessments with only the sense of hearing and resources available through the telephone. Clinical pearls are scattered throughout the text from those who have been "in the trenches" and cared for a wide variety of patients using the telehealth nursing techniques illustrated in this book. -- Provided by publisher.